Connecticut Fishways and Salmon Station: Progress Report - 1982 - Minta, P; Gephard, S; Becker, T; Van Nostrand, R (ScholarWorks@UMass Amherst, 1983)
Captures of adult Atlantic salmon were predictably low during this project period. The predicted returns to the Connecticut River were based on the quality and quantity of salmon smolts released in 1980. High losses of young salmon at the Pittsford National Fish Hatchery in 1979, attributed to a virulent strain of furunculosis, affected the two year classes yielding the 1980 and 1981 smolt releases. As a result low adult salmon returns to the Connecticut River system are also predicted for 1983. With the experience of the previous year's operation, the Adult Salmon Holding Station was operated under a more efficient regime resulting in decreased mortalities. One major contributing factor appears to be the development of a vaccine by Wildlife Vaccines of Wheatridge, Colorado which immunizes against furunculosis. Treatment procedures for control of other stress factors may have been timely because capabilities have been developed to identify and treat specific problems. Use of the fish passage facilities by other species of anadromous fishes has continued to be documented. The increase in American shad using the Rainbow Fishway resulted in numbers comparable to the first years of fishway operation. River herrings have been reluctant to pass through the Rainbow Fishway but have been utilizing the Leesville Fishway to some extent.